Research on Influence of Polyurethane Adhesive Modified by Polyurethane Filler Based on Recyclate - Kolar, Viktor; Muller, Miroslav (Manufacturing Technology Journal, 2018)
An adhesive bonding technology represents a prospective method of diverse materials connecting. Polyurethane (PUR) adhesives namely are used in an area of the adhesive bonding of wood and cellulose - based products. They gradually substitute formaldehyde-based adhesives. A higher reactivity of isocyanates with any compound having moving hydrogen namely, i.e. e.g. water, etc. is a significant disadvantage. An elimination of this negative factor is possible by adding a filler, e.g. PUR recyclate - based. The aim of the research is to determine an adhesive bond strength of the PUR adhesive modified with microparticles of crushed PUR foam (waste from a building - an insulation material). Improving of a tensile lap-shear strength and a material recyclation of the PUR foam are expected aims. Also a reduction of the adhesive price is a secondary output. Results of mechanical tests were supported by conclusions from a scanning electron microscopy (SEM) analysis with an aim to evaluate the interaction between the adhesive and the recycled filler. A diffusion of the adhesive into a wooden surface would occur at the wooden test samples and so mechanical properties of the modified adhesive would not be determined. This reason led to the research on the modification of the PUR adhesives LEAR D4, PP-6a17 and PP-7a within the adhesive bonded metal bond (a structural carbon steel S235J0). The research results proved a positive influence of the modification of the PUR adhesive with the microparticles of the PUR recyclate. The tensile lap-shear strength was increased. Results of SEM analysis proved a good wettability.
Keywords: Cyclic degradation; Elongation at break; SEM; Strength; Tensile test